Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Usaha Ternak Kambing di Kabupaten Pangandaran - Edi Sutardi; Firgian Ardigurnita; Nurul Frasiska (LPPM Perjuangan University of Tasikmalaya, 2022)
The purpose of this study is to determine the role of the government, motivation, capital, livestock ownership, land ownership, farmer education, livestock experience and the COVID-19 pandemic on the income of farmers in developing a business in Pangandaran Regency. By using two methods, namely observation and interviews. Observations were made by collecting data through direct observation of goat breeders in three sub-districts located in Pangandaran Regency. Interviews were conducted by collecting data by conducting direct interviews with goat breeders in Pangandaran Regency, which were more precisely conducted in three sub-districts. The parameters measured in the research that have been carried out are 8 factors, namely the role of the government, motivation, capital, livestock ownership, land ownership, farmer education, livestock experience and the covid-19 pandemic. The conclusion that can be drawn from this study is that there is a significant simultaneous influence of the independent variables, namely the role of government (X1), motivation (X2), capital (X3), livestock ownership (X4), land ownership (X5), farmer education (X6 ), experience (X7) and the covid-19 pandemic (X8) on the dependent variable (breeder income (Y) of 84.2%. Meanwhile, those that partially affect the income of farmers (one by one) are the capital factor (X3), the experience factor (X7) and the factor of the Covid-19 pandemic condition (X8). Keywords: Analysis; Goat; Factors; Income; Pangandaran